2019
DOI: 10.1002/ird.2369
|View full text |Cite
|
Sign up to set email alerts
|

The Blind Angle: Performance Assessment of Drip Irrigation in Use in a Large‐scale Irrigation Scheme in Morocco

Abstract: The need for lasting returns on the large investment in state‐sponsored drip irrigation projects and the ambitious objectives aimed to achieve requires thorough and continuous assessment of the performance of irrigation systems in use. However, few studies have evaluated the performance of systems once they have been installed, leading to overestimation of actual drip irrigation performance. This study focuses on the Tadla Irrigation Scheme, where a 10 000‐ha drip irrigation project had two objectives: improvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Clemmens et al (2008: 2) also underlined the importance of issues other than water saving in large‐scale conversion to drip and micro‐sprinkler irrigation in the Reedley/Dinuba area of central California (stone fruits) and drip irrigation in central Arizona (cotton) in the 1980s. Twenty years later, ‘Nearly all of that land has reverted to surface irrigation because the expected yield increases used to justify the added irrigation system cost did not materialize,’ Similarly, in Morocco studies in the Doukkala, Haouz and Tadla irrigation schemes have shown the difficulty of implementing collective drip irrigation projects and achieving water saving, but have also drawn attention to the multiple co‐benefits and drawbacks of the shift to drip irrigation (Bouazzama & Bahri, 2007; Boularbah et al, 2019; FAO, 2012; Molle & Tanouti, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clemmens et al (2008: 2) also underlined the importance of issues other than water saving in large‐scale conversion to drip and micro‐sprinkler irrigation in the Reedley/Dinuba area of central California (stone fruits) and drip irrigation in central Arizona (cotton) in the 1980s. Twenty years later, ‘Nearly all of that land has reverted to surface irrigation because the expected yield increases used to justify the added irrigation system cost did not materialize,’ Similarly, in Morocco studies in the Doukkala, Haouz and Tadla irrigation schemes have shown the difficulty of implementing collective drip irrigation projects and achieving water saving, but have also drawn attention to the multiple co‐benefits and drawbacks of the shift to drip irrigation (Bouazzama & Bahri, 2007; Boularbah et al, 2019; FAO, 2012; Molle & Tanouti, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This paper argues that the irrigation efficiency debate has overwhelmed other, more classical, engineering debates, in particular the relevance of different irrigation techniques for specific field conditions, and masked other co-benefits and drawbacks of the shift to pressurized irrigation. Taking a more nuanced stance on irrigation techniques, where different irrigation areas employing different irrigation techniques can coexist, enables, first, avoiding designing and implementing 'one size fits all' (drip) irrigation projects (see Lopez-Gunn et al, 2012), which may lead to disappointing results in terms of water conservation (Boularbah et al, 2019). Debating the respective (dis)advantages of irrigation techniques is a sound tradition in irrigation engineering (see for instance Lamm, 2002) and it is important to maintain a critical view of the fit of different irrigation techniques (Lopez-Gunn et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Technology alone is unlikely to result in improved irrigation management; on‐farm water application behaviours also need to be considered. The role of farmers' irrigation behaviours, however, has generally been neglected in the literature (Benouniche et al, 2014; Boularbah et al, 2019; Fernandez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These indicators mainly account for variations in pressure and discharge due to the quality of the drippers and to the hydrodynamic characteristics of the flows along driplines. However, few studies have specifically evaluated the perfor-mance of drip irrigation in use, resulting in underestimations or even completely disregarding the actual performance of drip irrigation and missing the opportunity of remedying existing problems in irrigation schemes with pressurized systems [10] [11].…”
Section: Introductionmentioning
confidence: 99%
“…Few authors have examined the actual performance of drip irrigation, mainly in individual drip projects [10] [15]. However, very little data are available on the performance of drip irrigation projects at the field level in large-scale or small irrigation schemes [11]. Specifically, very few data exist on the performance of drip irrigation system in Ghana particularly in the Upper West Region where the study was conducted.…”
Section: Introductionmentioning
confidence: 99%